Exploring Emerging Trends in AI-Driven Technological Advancements - Patil, Arya; Yadav, Shweta; Pandey, Manish (Etunas Sukses Sistem, 2024)
The rapid evolution of Artificial Intelligence (AI) has catalyzed a transformative wave across diverse technological landscapes. This study explores emerging trends in AI-driven technological advancements with a focus on developments within the Indian context. Through a mixed-methods approach combining literature analysis, expert interviews, and case studies from India's tech ecosystem, this research identifies key innovation patterns, adoption drivers, and sector-specific applications of AI technologies. Findings reveal significant momentum in areas such as healthcare diagnostics, smart agriculture, fintech automation, and personalized education, fueled by governmental initiatives, startup growth, and increased academic-industry collaboration. Additionally, the study highlights the challenges of ethical governance, data privacy, and digital divide that accompany rapid AI integration. By mapping the trajectory of AI's evolution in India, this research contributes to a deeper understanding of global AI dynamics and offers strategic insights for policymakers, researchers, and technology developers worldwide.